Caracterização de efluentes de viveiros de engorda de rã-touro (lithobates catesbeianus, Shaw, 1802) - Borges, Fernanda de Freitas [UNESP]; do Amaral, Luiz Augusto [UNESP]; de Stéfani, Marta Verardino [UNESP] (FapUNIFESP (SciELO), 2012)
Aim: Current analysis characterizes the effluent from bullfrog-rearing ponds during the grow-out phase; Methods: Temperature, pH, dissolved oxygen, electric conductivity, turbidity, total phosphorus, N-NH3, N-NO3, BOD5 and COD and the number of thermotolerant coliforms (Escherichia coli) of the inlet and outlet water of the ponds were analyzed twice a week. Assay consisted of a completely randomized experimental design with two treatments (inlet and outlet water) and six repetitions in a split-plot, coupled to collection over time as subplot; Results: All variables were significantly different (p < 0.05) between treatments and over time (p < 0.05). Average rates of temperature, pH and dissolved oxygen levels of the supply water were higher when compared to those of the effluent. The other variables such as conductivity, turbidity, total phosphorus, ammonia, nitrate, biological oxygen demand, chemical oxygen demand and E. coli were higher in the effluent when compared to rates in the supply water; Conclusions: The management during grow-out phase caused the deterioration of the water quality, with increasing levels of dissolved nutrients and the number of thermotolerant coliform. Ammonia and phosphorus levels in the effluent, caused by waste food, skin and feces, accelerate the eutrophication process of the receiving water body. Further studies on effluent treatment are required.
Characterization of effluents from bullfrog (Lithobates catesbeianus, Shaw, 1802) grow-out ponds
Keywords: Eutrophication; Nutrients; Raniculture; Water quality; Escherichia coli; Lithobates; Rana catesbeiana